Comparative study of binding of ovine complement factor H with different Borrelia genospecies - Kišová-Vargová, Lucia; Cerňanská, Dana; Bhide, Mangesh (Folia microbiologica, 2012)
This study presents the binding of ovine factor H (fH) by various serotypes of Borrelia and simultaneously correlates their complement resistance to sheep serum. Affinity ligand binding assay was employed to study the binding of borrelial proteins to ovine recombinant fH and its truncated forms (short consensus repeat, SCR 7 and SCRs 19-20). From a repertoire of 17 borrelial strains, only two strains showed affinity to sheep fH. A ~28-kDa protein of Borrelia burgdorferi sensu stricto (B. burgdorferi s.s., strain SKT-2) bound full-length fH as well as SCRs 19-20. This fH-binding protein was further identified as complement regulator-acquiring surface protein of B. burgdorferi (BbCRASP-1) by MALDI-TOF analysis. Surprisingly, a ~26-kDa protein of Borrelia bissettii (DN127) showed affinity to full-length fH but not to SCR 7 and SCRs19-20. In complement sensitivity assay, both strains-SKT-2 and DN127-were resistant to normal sheep serum. Significant complement resistance of two Borrelia garinii strains (G117 and T25) was also observed; however, none of those strains was able to bind sheep fH. Our study underscores the need of further exploration of fH-mediated evasion of complement system by Borrelia in domestic animals.
Keywords: bakteriální proteiny; komplement - faktor H; Molecular Sequence Data; Borrelia; lymeská nemoc; kinetika; molekulární sekvence - údaje; Animals; Sheep; Complement Factor H; ovce; nemoci ovcí; Sheep Diseases; Bacterial Proteins; Kinetics; zvířata; Lyme Disease